Radiotherapy for locally advanced resectable T3–T4 laryngeal cancer—does laryngeal preservation strategy compromise survival?. (28th November 2017) - Yamazaki, Hideya; Suzuki, Gen; Nakamura, Satoaki; Hirano, Shigeru; Yoshida, Ken; Konishi, Koji; Teshima, Teruki; Ogawa, Kazuhiko
Abstract: With the advancement of chemotherapy, a laryngeal preservation (LP) strategy was explored with the aim of improving maintenance of quality of life. Induction chemotherapy (ICT) following radiotherapy (RT) was considered a viable option because of its high initial response rate without hampering of overall survival (OS). Subsequently, concurrent chemoradiotherapy (CCRT) using CDDP became the standard of care for LP, showing the best LP ratio. For enhancing treatment intensity, ICT with taxan + CDDP + 5-FU (TPF-ICT) followed by RT showed superiority over ICT with CDDP + 5-FU (PF-ICT) followed by RT. Given that almost all randomized controlled trials investigating ICT include not only operable (endpoint, LP) but also inoperable (endpoint, OS) cases, physicians are faced with a dilemma regarding application in daily practice. In addition, increased treatment intensity causes augmentation of adverse events, which might reduce compliance. Thereafter, cetuximab, an effective drug with fewer adverse effects [bioradiotherapy (BRT)], emerged as another option. However, little evidence has confirmed its superiority over RT (or CCRT) in laryngeal cancer subpopulations. In spite of these developments, the OS of patients with laryngeal cancer has not improved for several decades. In fact, several studies indicated a decrease in OS during the 1990s, probably due to overuse of CCRT. Fortunately, the latter was not the case in most institutions. Currently, no other treatment has better OS than surgery. The eligibility criteria for LP and/or surgery largely depend upon the available expertise and experience, which differ from one institution to another. Therefore, a multidisciplinary team is required for the treatment of LP.